Au nanoparticle-decorated urchin-like TiO2 hierarchical microspheres for high performance dye-sensitized solar cells. (10th January 2019) - Li, Yuan; Zhou, Yusheng; Wang, Yong; Zhou, Ru; Ling, Qiang; Niu, Haihong; Zhang, Wei; Wang, Chaoqun; Qiu, Jihong; Guo, Zhiqiang; Xu, Jinzhang
Abstract: Urchin-like TiO2 hierarchical microspheres (UTHMs) with an extremely large surface area of 331 m 2 g −1 were synthesized via a facile one-pot hydrothermal method and studied for dye-sensitized solar cells (DSSCs) application. In-situ growth of Au nanoparticles (NPs) on the surface of the UTHMs were further conducted to achieve Au-decorated UTHMs (Au-UTHMs). A series of novel composite photoanode films were designed through the combined use of Au-UTHMs and UTHMs at different mass ratios. The DSSC constructed with the composite photoanode prepared under an optimal Au-UTHMs to UTHMs ratio of 2 wt% yields a considerable power conversion efficiency of 7.21%, which was markedly higher than that of the pure P25 NPs based device (5.19%) and pure UTHMs based device (6.10%). The significantly enhanced performance of the composite photoanode based DSSC can be attributed to the synergistic effect of two benefits: (1) the large specific surface area, strong light scattering and fast electron transfer channels arising from the novel hierarchical features of UTHMs, and (2) the enhanced light absorption owing to the localized surface plasmon resonance (LSPR) effect of Au NPs.